CAT Tools: The Challenge for Translation Learning in 4.0 Era - Atsani Wulansari (Universitas Muhammadiyah Semarang, 2018)
The rapid development of technology influences the teaching learning process nowadays. Teaching and learning process should be integrated with technology. One of the new paradigms in education system is education 4.0. It is the innovation on education which focuses on the use of information technology and the use of internet. There are many applications and websites which can be used as media of teaching learning process. As one of higher education subjects, Translation should apply such kind of technology. Translation technology is also developed time to time. Translation Industry nowadays requires the ability of using CAT Tool and it should be realized by translation lecturers. The students and lecturers have to be familiar with it. The background of this paper is based on the result of students’ interview. They are on the fourth semester and take Translation 2 in class 3 and 4. Based on the interview, the students are very familiar with machine translation such as Google Translate ILI, ImTranslator.net, sederet.com, and babla.co.id. In addition, the students are also familiar with Kamusku, online dictionary, and dictionary application on their smartphone. However, there is another technology that actually can be used in translation class. It is Computer-assisted translation or CAT tools. This paper tries to propose some technologies in translation that is called as CAT Tool. It is hoped that lecturers are able to apply them in the classroom.